THU0334 LASER SPECKLE CONTRAST ANALYSIS FOR MEASUREMENT OF PERIPHERAL BLOOD PERFUSION IN SYSTEMIC SCLEROSIS PATIENTS: CAN IT PREDICT FUTURE ISCHEMIC DIGITAL TROPHIC LESIONS?. (2nd June 2020) - Debusschere, C.; Vanhaecke, A.; Cutolo, M.; Deschepper, E.; Smith, V.
Abstract : Background: Vasculopathy is a hallmark of systemic sclerosis (SSc). Laser speckle contrast analysis (LASCA) is a research tool to assess peripheral blood perfusion (PBP) (1). At this moment, its reliability has been attested in SSc patients, but its predictive value for future ischemic digital trophic lesions (DTL) is unknown (1). Objectives: To investigate in an unselected, prospective SSc cohort if baseline LASCA PBP measurements can discriminate between patients who will develop ischemic DTL (iDTL) and those who will not. Methods: Patients (fulfilling 2013 ACR/EULAR criteria and/or 2001 LeRoy and Medsger criteria) were recruited during the period of December 2017 to September 2018. LASCA was performed at baseline, in standardized conditions (1). Regions of interest (ROIs) (diameter 1 cm) were outlined at the 2 nd -5 th fingertip both volar and dorsal. The 'average PBP' of these ROIs was calculated (expressed in arbitrary perfusion units [PU]). A monthly telephone survey was conducted for 1 year to investigate DTL occurrence. DTL were considered 'ischemic' if not related to calcinosis. Logistic regression and ROC analysis were used to assess if average PBP is predictive of future iDTL. Results: Of the 106 patients with complete follow-up (92 women [86, 8%]; 18 limited SSc [17, 0%], 82 limited cutaneous SSc [77, 4%], 6 diffuse cutaneous SSc [5, 7%]), 29 patients (27, 4%) had a DTL history. Forty-nine patients (46, 2%) were on vasodilator therapy. Only 7 patients developed at least 1 iDTL during follow-up (6, 6%) (Figure 1a ). Performing univariate logistic regression (ULR), average PBP was not predictive for future iDTL (Table 1 ). Of note, analyzing only the patients not taking vasodilators, average PBP in the 'iDTL group' (n = 3) was median 46, 8 PU (min. 45, 6 - max. 68, 8) vs. median 141, 4 PU (min. 24, 4 - max. 269, 5) in the 'no iDTL group' (n = 54) (Figure 1b ). In this subgroup, all 3 patients who developed iDTL (100%) had an average PBP ≤ 70 PU whereas only 9 of the 54 patients without iDTL development (16, 7%) had such PBP values. Conclusion: In this pilot study with an unselected day-to-day SSc population, where patients were allowed to continue vasodilators, there was an unexpected low iDTL incidence, undermining the power of our study. Even though, the observations in the subgroup of patients not taking vasodilators deserve future investigation to assess whether low PBP values, as measured by LASCA, are associated with a higher iDTL incidence. References: [1]Cutolo M, Vanhaecke A, et al. Autoimmun Rev. 2018;17(8):775-80. Disclosure of Interests: Claire Debusschere: None declared, Amber Vanhaecke: None declared, Maurizio Cutolo Grant/research support from: Bristol-Myers Squibb, Actelion, Celgene, Consultant of: Bristol-Myers Squibb, Speakers bureau: Sigma-Alpha, Ellen Deschepper: None declared, Vanessa Smith Grant/research support from: The affiliated company received grants from Research Foundation - Flanders (FWO), Belgian Fund for Scientific Research in Rheumatic diseases (FWRO), Boehringer Ingelheim Pharma GmbH & Co and Janssen-Cilag NV, Consultant of: Boehringer-Ingelheim Pharma GmbH & Co, Speakers bureau: Actelion Pharmaceuticals Ltd, Boehringer-Ingelheim Pharma GmbH & Co and UCB Biopharma Sprl